2012
DOI: 10.3389/fonc.2012.00014
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Polycyclic Aromatic Hydrocarbons Among Never Smokers in Golestan Province, Iran, an Area of High Incidence of Esophageal Cancer – a Cross-Sectional Study with Repeated Measurement of Urinary 1-OHPG in Two Seasons

Abstract: Studies have suggested a possible role of polycyclic aromatic hydrocarbons (PAHs) in the etiology of esophageal cancer in Golestan Province, Iran, where incidence of this cancer is very high. In order to investigate the patterns of non-smoking related exposure to PAHs in Golestan, we conducted a cross-sectional study collecting questionnaire data, genotyping polymorphisms related to PAH metabolism, and measuring levels of 1-hydroxypyrene glucuronide (1-OHPG), a PAH metabolite, in urine samples collected in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Elevated levels of carcinogenic PAH in the kitchen air and meat following frying meat have been reported elsewhere (14). A positive association between red meat intake and urinary 1-OHPG has also been reported in high-risk areas of Golestan (41). …”
Section: Discussionmentioning
confidence: 73%
“…Elevated levels of carcinogenic PAH in the kitchen air and meat following frying meat have been reported elsewhere (14). A positive association between red meat intake and urinary 1-OHPG has also been reported in high-risk areas of Golestan (41). …”
Section: Discussionmentioning
confidence: 73%
“…PAH is a carcinogen type A which is mostly associated with smoking and cooking methods such as barbecuing and grilling [19][20][21][22][23][24]. A recent case-control study reported an increased risk of PC associated with high intakes of various HCAs [25].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, wood-burning with subsequent release of polycyclic aromatic hydrocarbons (PAH) has been shown to be a risk factor in other settings. [11][12][13] On mycotoxins, our hypothesis was that m'gaiwa (whole grain maize flour), being the least processed type of local maize flour, harbours the most fumonisins and aflatoxins compared to other types of maize flour. Fumonisins and aflatoxins are types of mycotoxins produced by Fusarium and Aspergillus species of fungi, respectively, and have been associated with oesophageal cancer in other studies in the region, 8,[14][15] and in Iran.…”
Section: Introductionmentioning
confidence: 99%